Furans to Benzofurans: Intramolecular Cross-Benzoin Reactions Catalysed by N-Heterocyclic Carbenes - Shirke, Rajendra P.; Reddy, Virsinha; Anand, R. Vijaya; Ramasastry, S. S. V. (Synthesis, 2016)
The first synthesis of dihydrobenzofuranones and benzofurans based on an intramolecular cross-benzoin reaction has been reported. Commercially available 3-furan carboxaldehydes are readily α-alkylated to furnish 3-formyl-2-furylcarbinols, which are further elaborated to the synthesis of benzofurans in good yields through sequential bismuth(III) chloride catalysed furfurylation and a novel NHC-promoted intramolecular cross-benzoin condensation reaction.
Keywords: furans; N-heterocyclic carbenes; annulation; benzoin condensation; organocatalysis